Drug transport by red blood cells - Biagiotti, Sara; Perla, Elena; Magnani, Mauro (Frontiers in Physiology, 2023)
This review focuses on the role of human red blood cells as drug carrier. First of all, a general introduction about red blood cell physiology is provided, followed by the presentation of several cases in which RBCs act as natural carriers of drugs. This is due to the presence of several binding sites within the same RBCs and is regulated by the diffusion of selected compounds through the RBC membrane and by the presence of influx and efflux transporters. The balance between the influx/efflux and the affinity for these binding sites will finally affect drug partitioning. Thereafter, a brief mention to the pharmacokinetic profile of drugs with such a partitioning is given. Finally, some examples in which these natural features of human RBCs can be further exploited to engineer RBCs by the encapsulation of drugs, metabolites or target proteins, are reported. For instance, metabolic pathways can be powered by increasing key metabolites (i.e. 2,3-Bisphosphoglycerate) that affect oxygen release potentially useful in transfusion medicine. On the other hand, the RBC pre-loading of recombinant immunophilins permits to increase the binding and transport of immunosuppressive drugs. In conclusion, RBCs are natural carriers for different kind of metabolites and several drugs. Though, they can be opportunely further modified to optimize and improve their ability to perform as drug vehicles.